2021
DOI: 10.1186/s13059-021-02282-6
|View full text |Cite
|
Sign up to set email alerts
|

Homopolish: a method for the removal of systematic errors in nanopore sequencing by homologous polishing

Abstract: Nanopore sequencing has been widely used for the reconstruction of microbial genomes. Owing to higher error rates, errors on the genome are corrected via neural networks trained by Nanopore reads. However, the systematic errors usually remain uncorrected. This paper designs a model that is trained by homologous sequences for the correction of Nanopore systematic errors. The developed program, Homopolish, outperforms Medaka and HELEN in bacteria, viruses, fungi, and metagenomic datasets. When combined with Meda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 22 publications
0
97
0
Order By: Relevance
“…The developers of Homopolish tested the software’s polishing ability against bacterial genomes ( Enterococcus faecalis , Pseudomonas aeruginosa , Salmonella enterica , et al), a viral genome ( Lambda phage ), and a fungal genome ( Saccharomyces cerevisiae ). When combined with Medaka/HELEN, genome quality can exceed Q50 on R9.4 flow cells, achieving similar precision to that of hybrid assemblies with Unicycler [ 9 ]. Results showed that ONT-only sequencing could produce sufficiently high-quality microbial genomes for downstream analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developers of Homopolish tested the software’s polishing ability against bacterial genomes ( Enterococcus faecalis , Pseudomonas aeruginosa , Salmonella enterica , et al), a viral genome ( Lambda phage ), and a fungal genome ( Saccharomyces cerevisiae ). When combined with Medaka/HELEN, genome quality can exceed Q50 on R9.4 flow cells, achieving similar precision to that of hybrid assemblies with Unicycler [ 9 ]. Results showed that ONT-only sequencing could produce sufficiently high-quality microbial genomes for downstream analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The ONT assembly genome was polished using Illumina reads with Pilon and ONT reads with Medaka (v1.0.1 (accessed on 15 October 2020)). Then, Homopolish (v0.2.1 (accessed on 15 May 2020)) [ 9 ] was used to remove systematic indel errors from the genome polished by Medaka.…”
Section: Methodsmentioning
confidence: 99%
“…Current read-based error correction and polishing methods for ONT data primarily target genome assembly 17,18 . Raw read polishing has proven to be extremely effective in generating high quality assemblies, however, information supporting low frequency (less than 0.5) intra-host variants is almost always lost during the process.…”
Section: Main Textmentioning
confidence: 99%
“…Next, the filtered reads were assembled using Flye v2.8.3 ( 26 ), with five iterations of the polishing step (–iterations 5), generating a single circular draft assembly. The resulting assembly was aligned using bwa v0.7.17 ( https://github.com/lh3/bwa ) and polished sequentially using Racon v1.4.22 (-m 8 -x -6 -g -8 -w 500) ( 27 ), Medaka v1.4.3 ( https://github.com/nanoporetech/medaka ) (-m r941_min_hac_g507), and Homopolish v0.2.3 (-s bacteria.msh -m R9.4.pkl) ( 28 ). The quality of the genome assembly was evaluated using QUAST v5.1.0 ( 29 ).…”
Section: Announcementmentioning
confidence: 99%